The Influence Of Knowledge, Benefits, And Security On The Decision Of Islamic Banking Students Uinfas Bengkulu To Use M-Banking Bank Syariah Indonesia - Eka Sri Wahyuni Eka; Sofi Silvira Sofi; Rahmat Putra Ahmad Hasibuan Rahmat (Yayasan Darussalam Bengkulu, 2025)
The purpose of this study was to determine the effect of knowledge, benefits, and security on the decision of Uinfas Bengkulu Islamic Banking Students to use Bank Syariah Indonesia M-Banking. The research method used is quantitative with primary data collection techniques in the form of questionnaires distributed to 84 respondents. The data analysis technique was carried out using the Partial Least Square (PLS) method with the help of the SmartPLS 4.1.1.2 application. The results showed that simultaneously, based on the bootstrapping results and the coefficient of determination (R²) value, it can be concluded that the independent variables in the model as a whole have a significant influence on the dependent variable. Two of the independent variables make a significant contribution, while one other variable has no significant effect. With an R² value of 0.657, the model is able to explain 65.7% of the variation in the dependent variable, so this model is good enough and feasible to proceed to the partial testing stage and further analysis. The knowledge variable partially has a positive and significant effect on the decision of UINFAS Bengkulu Islamic Banking students to use Bank Syariah Indonesia m-banking. This is indicated by the tcount value of 2.126> from the t table of 1.96, it can be concluded that there is an influence between the knowledge variable on the decision of UINFAS Bengkulu Islamic Banking students to use Bank Syariah Indonesia m-banking, which is proven significant. The benefit variable partially has no effect on the decision of UINFAS Bengkulu Islamic Banking students to use Bank Syariah Indonesia m-banking. This is indicated by the tcount value of 1.920 < from the t table of 1.96, it can be concluded that there is no influence between the benefit variable on the decision of Islamic Banking students to use Bank Syariah Indonesia m-banking, which is proven to be insignificant. The security variable partially has a positive and significant effect on the decision of Islamic Banking students at UINFAS Bengkulu to use Bank Syariah Indonesia m-banking. This is indicated by the tcount value of 3.633> from the t table of 1.96, it can be concluded that there is an influence between the security variable on the decision of Islamic Banking students to use Bank Syariah Indonesia m-banking which is proven to be significant.